1996
DOI: 10.1002/etc.5620150302
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring for linear alkylbenzene sulfonates, dialkyltetralin sulfonates and their biodegradation intermediates

Abstract: Abstract-Concentrations of linear alkylbenzene sulfonates (LAS), dialkyltetralin sulfonates (DATS), and their biodegradation intermediates are reported for the influents and effluents of 10 U.S. domestic wastewater treatment plants as well as upstream and downstream river waters and sediments. Three types of treatment facilities in 10 U.S. states were sampled and analyzed. Removals were calculated based on initial concentrations of LAS and DATS. A derivatization electron capture/gas chromatography/mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…Similar values have been detected previously in other aquatic ecosystems in Spain, 8,10,16,18,28 the United States 29,42 and Germany. 43 For all the synthetic surfactants lower concentrations were found upstream (sampling station 1), in a part of the river that is free of urban and industrial activities.…”
supporting
confidence: 90%
“…Similar values have been detected previously in other aquatic ecosystems in Spain, 8,10,16,18,28 the United States 29,42 and Germany. 43 For all the synthetic surfactants lower concentrations were found upstream (sampling station 1), in a part of the river that is free of urban and industrial activities.…”
supporting
confidence: 90%
“…Concentrations of the surfactants ranged between 11.7 and 135 lg/L, while the degradation products were found from 0.3 to 3.1 lg/L. Trehy et al (1996) reported on levels of LAS and SPC in the USA, receiving waters upstream and downstream of domestic WWTP. The values averaged 16 and 35 lg/L for LAS, while the mean concentration of SPC amounted to 9.3 and 31 lg/L, respectively.…”
Section: Fate Of Surfactants In Waters and Soilsmentioning
confidence: 96%
“…Whereas anionic surfactants have been found at mg/kg levels in riverine and lake sediments, the corresponding degradation products were not detected in any instance (Trehy et al 1996). García et al (2005) studied the sorption of LAS homologues on anaerobic sludge and determined the distribution of each one between aqueous and solid phases and, consequently, its availability.…”
Section: Biodegradation Of Surfactantsmentioning
confidence: 98%
“…Alkyl chain lengths typically range from C10 to C14 with an average carbon chain length of ca 12. The phenyl attaches to the alkyl chain at all points with the exception of the primary carbon in the alkyl chain [13,14]. Our previous analysis showed that the LAS used in this work comprised of 1.9, 21.1, 37.0, 22.9 and 17.1% q0 to q4 homologues, respectively [19].…”
Section: Las and Its Stock Solutionmentioning
confidence: 99%
“…At the same time, it is also the most common pollutant found in almost all environmental fields [6][7][8][9]. LAS enters plantsoil systems by various routes including irrigation with water contaminated by LAS and with agricultural or municipal wastewater [10,11], application of manure or sludge on land [1,[12][13][14], and the use of detergent pesticides. LAS levels have been reported in the range: 1 mg kg -1 for soils without sludge amendment for two years [13] to as high as 47 mg kg -1 for soils shortly after application [1].…”
Section: Introductionmentioning
confidence: 99%